Development of BRUSLE hologram augmented reality based on Android apps by Engklek ethno-games Learning - Falah, Mochammad Faiz Nur; Rifqy, Muhammad Iqbal; Primrose, Ailsa Tsabita; Mukti, Taufiq Satria (Lembaga Pengembangan Publikasi Ilmiah dan Buku Ajar, Universitas Muhammadiyah Surakarta, 2025)
Curved Side Spaces (BRSL) in learning need to be presented with learning media to make it easier for students to understand the concept. This research aims to produce learning media based on technology and cultural values. The media in question is (BRUSLE) an Android application that can be accessed via mobile with augmented reality hologram content and integrated traditional Engklek game in the learning process. Development research was conducted using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The development was carried out based on a needs analysis at MTs N 2 Malang grade 7 in 2023 Mathematics Subjects on BRSL material. The developed product was carried out content validity by 3 experts (media, mathematics learning, and practitioners / teachers) to continue the feasibility test. The first stage feasibility test was conducted on 29 students from MTs N 2 Malang while the second stage feasibility test was conducted on 32 students from MTs N 3 Malang. product quality is interpreted through student questionnaire feedback after taking part in learning with BRUSLE. The quality of the product was also tested on the test results of students' comprehension skills. Data presentation is descriptive to describe the entire series of development process. The products produced in the development research can be concluded that BRUSLE Android APPS based on Hologram Augmented Reality on Engklek ethno-game-based learning is feasible and effective to use to improve students' concept understanding.